Relationship between gingival bleeding and blood glucose level: a case-control study - Sayeeganesh, N.; Baskar, P. K.; Manovijay, B.; Saranyan, R; Shanmugasundaram, N.; Vijayakumar, N (International Journal of Medical Research and Review, 2015)
Aim: To correlate the percentage of gingival bleeding sites and blood glucose levels in diabetic and non-diabetic patients. Materials and methods: a total of hundred patients participated in this case-control study. They were grouped in to two groups. Group 1 consisted of 50 type II diabetic patients and group II consisted of 50 non-diabetic patients. Post prandial blood glucose levels oral-hygiene index and percentage of sites with bleeding on probing were recorded. The results obtained were analysed statistically using students‘t’ test. Results: Bleeding tendencies were more in diabetic patients compared to non-diabetic patients.It was found to be highly statistically significant (P<0.01). Conclusion: The study suggested the association of gingival bleeding to the blood glucose level. Blood glucose level reflects their metabolic rates.